Correlation of Physical Condition Components with Volleyball Smash Ability (Overview of Arm Explosive Power, Leg Explosive Power and Eye-Hand Coordination) - Hakim, Hikmad; Nawir, Nukhrawi; Bismar, Ahmad Rum (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This study aims to determine the correlation of arm explosive power, leg explosive power and hand-eye coordination with smash ability in volleyball games of FIK UNM students. The population in this study was all sports coaching education students of FIK UNM with a total research sample of 30 students selected by random sampling. The data analysis techniques used are correlation and regression analysis techniques using the SPSS Version 16 system at a significant level of 95% or α 0.05. Departing from the results of data analysis, this study concluded that: (1) the correlation of arm explosive power with smash ability in volleyball games, proven r0 = 0.955 (P < α 0.05), (2) the correlation of leg explosive power with smash ability in volleyball games., proven r0 = 0.957 (P < α0.05), (3) correlation of hand-eye coordination with smash ability in volleyball games., proved r0 = 0.852 (P < α0.05), (4) correlation of arm explosive power, leg explosive power and hand-eye coordination with smash ability in volleyball games., proven R0 = 0.970 (P < α 0.05). It can be explained that if a student is supported by a good correlation of arm explosive power, leg explosive power and hand-eye coordination, the student can smash volleyball games well too. Based on the results of the above research can be concluded: 1) There is a significant correlation between arm explosive power with smash ability in volleyball games, 2) There is a significant correlation between leg explosive power with smash ability in volleyball games, 3) There is a significant correlation of hand-eye coordination with smash ability in volleyball games, and 4) There is a significant correlation of arm explosive power, Leg explosive power and hand-eye coordination with smash ability in volleyball games at FIK UNM Students.